On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern EuropeOn the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe - Surugiu, Victor (Zootaxa, 2016)
In order to clarify taxonomic problems relating to the identity of Scolelepis (Scolelepis) specimens from the Black Sea, the identified material was compared with specimens of Scolelepis cirratulus (Delle Chiaje, 1829) from the Mediterranean, of S. squamata (Abildgaard, in O.F. Müller, 1806) from the North Sea and the Atlantic coast of Spain, and with the syntypes of S. mesnili (Bellan & Lagardère, 1971) from the Atlantic coast of France. The examination of a large number of specimens (both juveniles and adults) reveals that the currently accepted morphological differences distinguishing all species show size-related patterns, suggesting that they all belong to one species. Therefore, this study supports the view that Scolelepis cirratulus and Scolelepis mesnili are junior synonyms of Scolelepis (Scolelepis) squamata. As a result of the re-assessment of the species limits of Scolelepis (Scolelepis) squamata, a new species, Scolelepis (Scolelepis) neglecta sp. nov., is distinguished and described from the Cantabrian coast of Spain. It inhabits shallow sublittoral fine sands and was earlier misidentified and reported from the Atlantic coast of Europe and the Mediterranean Sea as Scolelepis squamata, Scolelepis mesnili, Scolelepis cantabra (Rioja, 1918), or Dispio uncinata Hartman, 1951. The new species is characterized by having a trilobate prostomium with an acuminate medial portion, a short peristomium with well-developed dorso-lateral wings, short palps with two longitudinal bands of elevated lobes, neuropodial postchaetal lamellae notched from chaetigers 14–41, and strongly curved bidentate neuropodial hooded hooks with a slight constriction on the shaft starting from chaetigers 19–49. The morphology, diagnostic characters and ecology of both Scolelepis (Scolelepis) squamata and Scolelepis (Scolelepis) neglecta sp. nov. are discussed.